2018
DOI: 10.51894/001c.6516
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Factors Associated with Septic Shock Mortality Risks

Abstract: The presence of at least one underlying chronic health condition, such as long-term care facility residence, malnutrition, immunosuppression, or prosthetic device use, are well known factors increasing infection risks and progression to severe sepsis. Furthermore, some degree of cardiovascular dysfunction occurs in the majority of septic patients and this prognostic significance has become increasingly recognized. Since septic shock carries the highest mortality risk on the sepsis spectrum, it is important to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…After searching the electronic databases, 18001 publications were retrieved. Following thorough examination according to the inclusion and exclusion criteria, 10 studies (35712 patients in total) published between 2012 and 2021 were finally included in the meta-analysis[ 4 , 6 , 9 , 11 , 12 , 19 - 23 ]. A PRISMA flow chart of the study is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After searching the electronic databases, 18001 publications were retrieved. Following thorough examination according to the inclusion and exclusion criteria, 10 studies (35712 patients in total) published between 2012 and 2021 were finally included in the meta-analysis[ 4 , 6 , 9 , 11 , 12 , 19 - 23 ]. A PRISMA flow chart of the study is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are reported in Table 1 . Of the ten included studies, five studies were conducted in the United States[ 4 , 6 , 11 , 12 , 22 ] and the remaining five studies were from the Republic of China[ 9 ], Macedonia[ 19 ], France[ 20 ], Israel[ 21 ] and Japan[ 23 ]. Three of the studies were prospective studies[ 4 , 19 , 20 ] and the other seven were retrospective studies[ 6 , 9 , 11 , 12 , 21 - 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies reported short-term mortality (Figure 2). 9,10,15,[19][20][21][22][23][24][25] The pooled OR of short-term mortality associated with the premorbid use of beta-blockers was 0.85 (95% CI, 0.69-1.04; P = .12, I 2 = 50%). Five studies reported an adjusted OR of short-term mortality; the pooled adjusted OR of short-term mortality associated with the premorbid use of beta-blockers was 0.73 (95% CI, 0.65-0.83; P < .001, I 2 = 0%).…”
Section: Primary Outcomementioning
confidence: 99%
“…10,20,22,25 There were no significant differences in the ICU LOS (SMD, 0.05; 95% CI, −0.07-0.18; P = .38; I 2 = 68%) and need for mechanical ventilation (OR, 1.14; 95% CI, 0.69-1.90; P = .61; I 2 = 80%). Five studies reported the HR on admission 9,21,[23][24][25] and lactate levels on admission. 9,10,20,23,24 HR on admission (SMD, −0.33; 95% CI, −0.50-0.16; P < .001; I 2 = 66%) and lactate level on admission (SMD, −0.25; 95% CI, −0.36-0.13; P < .001; I 2 = 49%.)…”
Section: Secondary Outcomesmentioning
confidence: 99%